Exploring an artificial intelligence–based, gamified phone app prototype to track and improve food choices of adolescent girls in Vietnam: Acceptability, usability, and likeability study - Braga, Bianca C.; Nguyen, Phuong Hong; Aberman, Noora-Lisa; Doyle, Frank; Folson, Gloria; Hoang, Nga Thu; Huynh, Phuong; Koch, Bastien; McCloskey, Peter; Tran, Lan; Hughes, David; Gelli, Aulo (JMIR Publications, 2022)
Background: Adolescents’ consumption of healthy foods is suboptimal in low- and middle-income countries. Adolescents’ fondness for games and social media and the increasing access to smartphones make apps suitable for collecting dietary data and influencing their food choices. Little is known about how adolescents use phones to track and shape their food choices. Objective: This study aimed to examine the acceptability, usability, and likability of a mobile phone app prototype developed to collect dietary data using artificial intelligence–based image recognition of foods, provide feedback, and motivate users to make healthier food choices. The findings were used to improve the design of the app.